Design and Implementation of a Web-Based Internship Management Information System for Vocational Education - Muhamad Tegar Putra Perdana; Geovanne Farell; Titi Sriwahyuni; Lativa Mursyida (Jurnal Vokasi Teknik Informatika, 2025)
The integration of information technology in vocational education plays a vital role in improving the effectiveness and efficiency of practical learning programs such as Field Work Practice (PKL). This study aims to develop a web-based internship management information system that supports the organization, supervision, and evaluation of PKL activities in vocational high schools. The system was developed using the Laravel framework with PHP as the programming language and MySQL as the database management system. The Waterfall method was adopted to ensure a structured and systematic development process. Key features of the system include real-time student attendance tracking through selfie verification with geolocation, a digital daily journal, an integrated assessment mechanism, and automated certificate generation accessible by both school and industry mentors. The implementation of the system at SMK Negeri 2 Padang demonstrates its effectiveness in reducing the accumulation of physical documents and enhancing the monitoring and administration of internship activities. The results highlight the system's potential to improve the quality of internship management and provide a model for similar implementations in other vocational institutions.